2016
DOI: 10.4103/0253-7176.185953
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive-Compulsive Disorder Presenting with Compulsions to Urinate Frequently

Abstract: Obsessive compulsive disorder (OCD) is a common psychiatric disorder which is easily recognized. However, sometimes patients of OCD present in such an atypical presentation of symptoms and a pathway to care involving multiple specialities. We report a case of a girl who had consulted several physicians and a urologist for frequent micturition, who was treated as a case of OCD after clarifying the compulsive nature of her symptom. There was significant improvement in her condition following 8 weeks of treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
2
6
0
Order By: Relevance
“…We hence concluded that such urinary disorders may be a side effect of OCD in its acute phase or untreated chronic OCD. The patient's urodynamic evaluation revealed detrusor underactivity 20 . Several similar cases were discovered in the current study.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…We hence concluded that such urinary disorders may be a side effect of OCD in its acute phase or untreated chronic OCD. The patient's urodynamic evaluation revealed detrusor underactivity 20 . Several similar cases were discovered in the current study.…”
Section: Discussionsupporting
confidence: 84%
“…At the same time, there was no urinary frequency in the OCD group, although many of them had infrequent urination and complained of urgency (sensory urgency or urge incontinence). Nonetheless, in a 2016 study conducted by Jiwanmall and Kattula, 20 OCD patients presented with urinary frequency and pollakiuria. 20 This study found that OCD patients delayed micturition for an extended period, most likely to avoid dealing with their compulsions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are frequently comorbid in children with attentional and obsessive-compulsive (OC) disorders [ 5 , 6 , 7 ]. Some case reports have suggested that urination could be a form of compulsion [ 8 , 9 ]; cognitive behavioural therapy (CBT) has long been applied in the treatment of functional urinary disorders [ 10 ]. It has also been hypothesized that these conditions may at least share some common neuropharmacological pathways involving stress-related peptide corticotropin-releasing factor (CRF) and CRF-related peptides [ 11 ], and the treatment of one may improve the other.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps urologists (and more importantly, primary care physicians) should be routinely screening their patients with BBD for conditions such as anxiety, attention deficit, depression, and obsessive-compulsive disorder. [2][3][4][5][6][7][8][9] Focusing on these diagnoses, with known effective treatments, before investigating and treat-ing the end organ might prove more beneficial for patients and less frustrating for urologists.…”
mentioning
confidence: 99%